Effects of receptor tyrosine kinase inhibitors on VEGF165a- and VEGF165b-stimulated gene transcription in HEK-293 cells expressing human VEGFR2 - Carter, Joanne J.; Wheal, Amanda J.; Hill, Stephen J.; Woolard, Jeanette (Wiley, 2015)
BACKGROUND AND PURPOSE: Receptor tyrosine kinase inhibitors (RTKIs) targeted at VEGF receptor 2 (VEGFR2) have proved to be attractive approaches to cancer therapy based on their ability to reduce angiogenesis. Here we have undertaken a quantitative analysis of the interaction of RTKIs and two VEGF splice variants, VEGF165a and VEGF165b, with VEGFR2 by studying nuclear factor of activated T-cells (NFAT) reporter gene activity in live HEK-293 cells. EXPERIMENTAL APPROACH: HEK-293 cells expressing the human VEGFR2 and a firefly luciferase reporter gene regulated by an NFAT response element were used for quantitative analysis of the effect of RTKIs on VEGF165a- and VEGF165b-stimulated luciferase gene expression. KEY RESULTS: VEGF165a produced a concentration-dependent activation of the NFAT-luciferase reporter gene in living cells that was inhibited in a non-competitive fashion by four different RTKIs (cediranib, pazopanib, sorafenib and vandetanib). The potency obtained for each RTKI from this analysis was similar to those obtained in binding studies using purified VEGFR2 kinase domains. VEGF165b was a lower-efficacy agonist of the NFAT-luciferase response when compared with VEGF165a. Analysis of the concentration–response data using the operational model of agonism indicated that both VEGF165 isoforms had similar affinity for VEGFR2. CONCLUSIONS AND IMPLICATIONS: Quantitative pharmacological analysis of the interaction of VEGF165 isoforms and RTKIs with VEGFR2 in intact living cells has provided important insights into the relative affinity and efficacy of VEGF165a and VEGF165b for activation of the calcineurinNFAT signalling pathway by this tyrosine kinase receptor.